Characterization and recycling of raw fly ash derived through stems of Sesamum indicum as a proficient adsorbent for chlorazol black E from wastewater - Muhammad Rafique; Shahzad Ali Shahid Chatha; Adnan Ali; Sanam Sadiq; Tabassum Hussain (Kuwait Journal of Science)
Coal fly ash (CFA) is an anthropogenic industrial byproduct that is expected to increase exponentially to fulfill the needs of energy using coal and agro-waste as a cheap fuel. The disposal of this classified human carcinogen is a major concern in developing and underdeveloped economies due to lack of resources. Recycling and value addition of industrial waste, coherence with sustainable development goals is a viable solution. Zeolitization of coal fly ash is an ideal approach for recycling this waste into superior products to be used in a variety of industrial applications. This study was aimed to recycle CFA to useful zeolites using ultrasound assisted hydrothermal process. Sesamum indicum plant stems based fly ash (rFA) was found to belong to class “F" and has very low moisture and carbon contents. To investigate the morphology and elemental composition of rFA and UHSZ, SEM/EDX was used along with XRD, FTIR and Raman spectroscopy which confirmed the existence of quartz, mullite and anhydrite. SEM/EDX results revealed the presence of Al, Si, S, K, Sb, Mg and Ta in raw ash. Adsorption studies of both rFA and synthesized zeolite(UHSZ) were conducted to determine the quintessential parameters of pH, time, initial dose of adsorbent for optimum results. Fabricated zeolites (2 ​g/100 ​mL) from raw fly ash removed 90–98% of chlorazol black E (DB38) from 100 ​mg/L solution within 40 ​min at pH ​≈ ​7. Both Langmuir and Freundlich isotherms gave best fit, which validated that the adsorption of DB38 to UHSZ was a blended process rather than a simple monolayer adsorption mechanism. Pseudo 1st-order and 2nd-order kinetic models were adopted to fit the obtained kinetic data. The pseudo 2nd-order kinetic model was found to be most related.